Effectiveness of existing noise barriers: comparison between vegetation, concrete hollow block, and panel concrete - Halim, Herni; Abdullah, Ramdzani; Abang Ali, Abang Abdullah; Mohd Nor, Mohd Jailani (Elsevier, 2015)
Noise barrier is used to shield receivers from noise especially road traffic noise. In Malaysia, there is lack of literature regarding noise barriers including the effectiveness of noise barrier that has been erected. This study investigates the effectiveness of existing noise barriers; vegetation, concrete hollow block and panel concrete at three urban residential areas in Klang Valley region. Insertion loss is used to identify the effectiveness of selected noise barriers. The finding indicates that panel concrete provides consistent insertion loss and exceed the minimum value of effective noise barrier followed by concrete hollow block and vegetation.